CHALLENGES OF THE 21ST CONSTITUTIONALISM: FOOD SOVEREIGNTY AS A CONSTITUTIONAL GUARANTEE OF THE FUNDAMENTAL RIGHT TO FOOD (Revista Paradigma, 2020)
Taking in consideration the perspective of constitutional theory and the field comparative constitutional law, using the comparative method in a dialogical approach, this article, which presents partial outcomes of researches in progress regarding the challenges of 21st century constitutionalism, aims to provide theoretical efforts for a critical reflection on the right to food and food sovereignty, focusing the Latin American context and two recent constitutions: Constitution of Ecuador (2008) and Constitution of Bolivia (2009). Therefore, the article is divided in three sections: 1. The fundamental right to food, food security and food sovereignty; 2. Efforts form comparative constitutional law: right to food and sovereignty in the State of Buen Vivir; 3. Challenges and risk factors for food sovereignty in Latin America.